Exploring potentials of indigenous yeasts in fermentation of Chambourcin Grapes. Issue 7 (10th July 2020) - Tang, Chun; Wee, Josephine
Abstract : Background: Indigenous yeasts present on grape berries have been shown to impact the winemaking process and final wine quality. In this study, we used Chambourcin, a hybrid grape cultivar, to isolate indigenous yeasts for potential use in winemaking. Hybrid grapes are of particularly interest due to higher resistance to cold temperature and fungal diseases. Methods: Yeasts were isolated from spontaneous fermentation of crushed grapes by plating on Dichloran Rose Bengal Chloramphenicol agar and identified by Sanger sequencing. Yeast candidates were selected for their ability to grow in Yeast Extract-Peptone-Dextrose broth supplemented with varying ethanol concentration. Candidate yeasts were chosen for mock fermentation using sterile Chambourcin juice. Volatile and non-volatile compounds that predict wine quality (flavor and aroma) were measured by UPLC and GC-MS. Results: Hanseniaspora uvarum, Starmerella bacillaris, Candida californica, and Zygoascus meyerae were predominantly isolated from Chambourcin. S. bacillaris isolate 180002 and C. californica isolate 180004 were able to tolerate up to 10% ethanol compared to S. cerevisiae (ethanol tolerance up to 12%). Our results demonstrate that isolate 180002 grown in ethanol supplemented medium is comparable to the commercial S. cerevisiae . Various aroma profiles of three main chemical families – esters, higher alcohol and volatile acids in products fermented by S. bacillaris and other isolates were observed. Conclusion: Starmerella bacillaris isolate 180002 demonstrates potential for use in winemaking with hybrid grapes based on ethanol tolerance and production of wine related chemical compounds. This study further supports the application of indigenous grape-associated yeasts in creating flavor and aroma diversity of wine.